iPad made simple - Trautschold, Martin; Mazo, Gary.; Safari eBooks ([New York] : Apress, 2010)
"Get the most out of your iPad with iPad Made Simple--learn all the key features, understand what's new, and utilize dozens of time-saving tips and tricks. This book includes over 740 pages of easy-to-read instructions and over 1,000 carefully annotated screen shots to guide you to iPad mastery"--Resource description page.
Description based on print version record.
Includes index.
Keywords: iPad (Computer); Portable computers; Apple computer; Electronic books